Work-Life Balance and Employee Performance: The Mediating Roles of Job Engagement, Satisfaction, and Stress : A Case in an Indonesian Private University - Marpudianto, Kharis; Yuniningsih, Yuniningsih; Rini, Hesty Prima (Majalah Ilmiah Bijak, 2025)
The performance of educators is a crucial factor in achieving the effectiveness of educational institutions. However, in recent years, the performance of educators at X University in Surabaya has declined. One factor suspected to influence performance is work-life balance. This study aims to analyze the effect ofWork-life balance on employee performance, both directly and through job engagement, job satisfaction, and job stress as mediating variables. This study employs a survey method to analyze the influence of work engagement, job satisfaction, and work stress on the performance of educators at Wijaya Kusuma University Surabaya. Data were collected using a systematically designed questionnaire to measure these variables. The results indicate thatWork-life balance contributes to improving employee performance. Job engagement and job satisfaction strengthen this relationship, while job stress can hinder optimal performance achievement. Therefore, educational institutions need to implement policies that support a balance between work and personal life, such as flexible work arrangements and stress management programs, to create a more productive and conducive work environment.